Effect of Laser Shock Peening on the Fatigue Behavior and Mechanical Properties of Composite Materials - Al-Khazraji, Ahmed N.; Mutasher, Ammar A. (Al-Khwarizmi Engineering Journal, 2019)
In this study, Laser Shock Peening (LSP) effect on the polymeric composite materials has been investigated experimentally. Polymeric composite materials are widely used because they are easy to fabricate and have many attractive features. Unsaturated polyester resin as a matrix was selected and Aluminum powder with micro particles as a reinforcement material was used with different volume fraction (2.5%, 5% and 7.5%). Hand lay-up process was used for preparation the composites. Fatigue test with constant amplitude with stress ratio (R =-1) was carried out before and after LSP process with two levels of energy (1Joule and 2Joule). The result showed an increase in the endurance strength of 25.448% at 7.5% volume fraction when peened is 1J laser energy. Also, the ultimate strength and Young’s modulus were increased by 6.474% and 10.588% respectively after LSP with the same laser energy.  On the other hand, composites with (2.5% and 5%) volume fraction manifested a reduction in the mechanical and fatigue strength especially when treated by 2J laser energy.